Relationship Between Knowledge and Hypertension History with Blood Pressure Control in Elderly - Destiara Hesriantica Zaenurrohmah; Riris Diana Rachmayanti (Universitas Airlangga, 2017)
Hypertension is a main cause of morbidity and mortality in Indonesia, thus the treatment of this disease commonly done in every level of health facilities. Based on Riskesdas 2013 the most diseases toward elderly is Hypertention up to 57.6% followed by arthritis (51.9%) and stroke (46.1%). Based on blood pressure measurement in Posyandu Melati known most of elderly have prehypertension. This research aimed to analyze the relationship between knowledge, hypertention history and blood pressure control of elderly in Posyandu Melati, Ampel sub district, Semampir distric, Surabaya City. This research was an observational research with cross sectional approach. Subjects of the research were drawn from the population using total population with inclusive criteria was elderly that had come to the Posyandu Melati. Number of samples obtained was 50 elderies. Primary data were collected using questionnaires. Analysis data has done using univariate and bivariate analysis. After being analyzed, data processed by chi square statistical test. The result of bivariate analysis was found that variables associated with hypertension history and blood pressure control (p = 0.019). The conclusion which could be drawn were knowledge was unassociated with blood pressure control. Hypertension history has low associated with blood pressure control. There is needs of education or health promotion for elderlies through counseling and medias. Keywords: knowledge, hypertension history, blood pressure control